The Heterogeneous Impact of Organic Fertilizer Adoption on Household Welfare in Rice Production in Vietnam - Phan, Nguyen Thai; Kien, Nguyen Duc; Dung, Tran Cong; An, Le Thanh; Dinh, Nguyen Cong (AGRARIS: Journal of Agribusiness and Rural Development Research, 2025)
Despite growing interest in sustainable agriculture, the impact of organic fertilizer adoption on household welfare in Vietnamese rice production remained underexplored. This study addressed this knowledge gap by examining its effect on productivity, total output, revenue, assets, and food security (household food diversity index and food expenditure). The data originated from the Vietnam Household Living Standard Survey (VHLSS) conducted in 2020. After merging data from VHLSS, 2,059 observations in rice production were employed to unveil the relationship between variables. To mitigate selection bias, propensity score matching (PSM) was utilized to assess the average treatment effect on the treated population. The results uncovered that households utilizing organic fertilizers exhibited a superior food diversity index and greater food expenditure but lower productivity and total assets than their counterparts. These findings underscored the necessity of enhancing organic fertilizer utilization in rice farming, facilitating food security in rice production in rural Vietnam. Accordingly, smallholders should be encouraged to utilize organic fertilizers, and the government should assist farmers by providing training and enhancing their expertise in applying organic fertilizers.